Granular Cell Tumor and Spindle Cell Oncocytoma of the Pituitary Gland: Imaging and Intraoperative Cytology Diagnostic Dilemmas and Management Challenges - Kandregula, Sandeep; Shashidhar, Abhinith; Rao, Shilpa; Beniwal, Manish; Shukla, Dhaval; Srinivas, Dwarakanath; Saini, Jitender; Mahadevan, Anita; Santosh, Vani; Arimappamagan, Arivazhagan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Tumors arising from the posterior pituitary gland are rare and closely resemble pituitary adenoma in presentation and imaging. Most of them come as a histopathologic surprise. We have analyzed the posterior pituitary tumors managed in our institute and have discussed the dilemmas in imaging, challenges in intraoperative squash cytology, and surgical management.Methods We retrospectively reviewed our operative database of pituitary tumors over the past 10 years, which included five posterior pituitary tumors (three granular cell tumors [GCTs] and two spindle cell oncocytomas [SCOs]). Clinical, imaging, and endocrine characteristics; intraoperative details; histopathologic features; and postoperative outcomes were collected and analyzed.Results The mean age of the patients was 47 years. All patients presented with varying degrees of vision loss. Radiology revealed a sellar / suprasellar lesion with the pituitary gland seen separately in two of three GCTs, whereas a separate pituitary gland could not be identified in both the SCOs. Pituitary adenoma was a radiologic diagnosis in only two of five cases. Three patients underwent a transsphenoidal surgery, whereas two underwent surgery by the transcranial approach. Intraoperative cytology was challenging, though a possibility of posterior pituitary tumor was considered in three of four cases, whereas one was considered meningioma. All the tumors were very vascular and influenced the extent of resection.Conclusions GCTs and SCOs are relatively uncommon tumors that are difficult to diagnose on preoperative imaging. Intraoperative squash cytology too can pose challenges. A preoperative suspicion can prepare the surgeon for surgery of these hypervascular tumors. The transcranial approach may be necessary in cases of uncertainty in imaging.
Keywords: granular cell tumor; spindle cell oncocytoma; intraoperative cytology; surgery; imaging